Discussion to Improved Understanding: The TNI Role in Helping Villages for Community Empowerment in the Border Area of Nusa Tenggara Timur - Posma Sariguna Johnson Kennedy (Journal of Sustainable Community Development (JSCD), 2022)
The most difficult 'enemy' to face on the Indonesian border in the Province of Nusa Tenggara Timur (NTT) and the State of Timor Leste is poverty. We can only fight poverty with community empowerment. Community empowerment at national borders is one of the Indonesian National Armed Forces (TNI). The method of implementing this activity is to conduct discussions to increase understanding of the TNI's duties to assist local governments in community empowerment programs in the border areas of NTT. The method of writing this paper is to use a qualitative approach by reviewing various literature and discussions conducted with Korem 161/Wirasakti Kupang and Kodim 1605 Belu NTT. At the NTT border, the Border Security Task Force (Satgas Pamtas) 742/SWY TNI performs the main task of Border Security and explores the community's potential, and empowers this potential. There are many creations of this unit in "fighting poverty," namely through the five programs of the Wira Yudha House. Rumah Wira Yudha has programs in Education, Health, Love Pancasila, Entrepreneurship, and Wira Yudha Sharing to answer the needs and limitations in border villages. All these activities are full of activities based on Pancasila values.